Rhetorical Structures of Beauty Brands Sales Videos on Instagram - Mulyani, Sri; Warsidi, Warsidi; Tahir, Tahir; Kamal, Alfiandy (English Literature Studi Program Universitas Islam Makassar, 2025)
This study analyze the rhetorical structures employed in beauty brand sales videos on Instagram aiming to understand how they engage viewers and influence purchasing behaviour. Using a genre-based analytical approach, especially the model suggested by (Warsidi, Adnan, et al., 2024), the study identifies three main rhetorical moves across 15 selected sales videos. These videos were chosen based on data sets criteria. The findings reveal that establishing customer interest is the most dominant move in all samples, with strategies such as presenting product benefits and using persuasive interaction language appearing most frequently. Conversely, strategies like greeting the audience or providing taglines appeared less often and were considered optional. The study explores language frames used to increase engagement on social media platforms, including emotionally resonant queries, descriptive product language, personal suggestions, and urgent calls to action. By combining qualitative and quantitative methods, this study provides valuable insights into how rhetorical strategies influence consumer behavior on social media platforms. The research emphasizes the importance of creating content and the strategic role of language and appearance in selling products effectively. This research contributes to understanding digital marketing and offers implications for rhetorical studies, social media marketing, and English for Business Purposes (EBP).